Să se efectueze:

(– 2)3 – (– 5)2 + (– 60) =

(– 2)3 – (– 4)2 + (– 50) =

(– 70 ) + (– 3)3 – (– 2)3 =

(– 6)2 – (– 4)2 + (– 80) =

(– 54)3 · (+ 5)7 : (– 25)9 + (–52)=

(– 2 )3–(– 7)2+(– 50)=

(– 3 )7 · (– 32)5 : (– 9)8 + (– 32) =

(– 24 )3 ·(+ 2)5:(– 4)8+(–22 )=

(+ 2)7 · (– 22)6 : (– 4)9 + (– 22) =

(–7 0 )–(– 2)2+(– 3)2=

(– 3 )9·(– 32)5:(– 9)9+(– 32)=

(– 5 )7·(– 52)3:(– 25)6+(– 52)=

(– 24 )3·(– 2)9:(– 4)10+(– 22)=

(– 3)5 (– 34)3 : (– 9)8 + (– 32) =

(+ 2)9·(– 22)5:(– 4)9+(– 22)=

(– 3)7·(– 32)7:(– 9)10+(–32)=

5-(+5)2×2575:[(-53)]50=

-56:(2-7)6-252:55+(-1)26=

(– 5 )7·(– 52)3:(– 25)6+(– 52)=

(2 )7·(– 22)6:(– 4)9+(– 22)=

(– 54)3·(+ 5)7:(– 25)9+(–52)=

(– 24)3·(+ 2)5:(– 4)8+(– 22)=

 

Să se efectueze:

– 2·(– 1)n–3·(– 1)2n+1– 5·(– 1)n+1 ;[image]

– 4·(– 1)n –2·(– 1)n +1–5·(– 1)2n ;[image]

–5·(– 1)n+1–2·(– 1)n –3·(– 1)2n+1; [image]

– 4·(– 1)n–2·(– 1)2n– 3·(–1)n+1;[image]

– 6·(– 1)n–2·(– 1)n+1–3·(– 1)2n; [image]

– 2·(– 1)n+1–3·(– 1)n–5·(– 1)2n+1; [image]

– 4·(– 1)n–5·(– 1)2n–3·(– 1)n+1;[image]

– 6·(– 1)n+1–2·(– 1)2n+1–3·(– 1)n; [image]

– 2·(– 1)n 4·(– 1)2n+1–5·(– 1)n+1;[image]

–6·(–1)n–3·(– 1)2n–2·(– 1)n+1; [image]

3-(-1)k-(-1)k+3-(-1)2k+4+(-3)0-03=

 

 

Să se efectueze:

(– 1 )1·(– 1)2·(– 1)3 · … · (– 1)30=

(– 1)1 + (– 1)2 + (– 1)3 + … + (– 1)21 =

(– 1)1 + (– 1)3 + (– 1)5 + … + (– 1)21 =

(– 1)1 · (– 1)3 ·(– 1)5· … ·(– 1)25=